2019
DOI: 10.1088/2399-6528/ab12a9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing molecular simulation for the analysis of lipid monolayer reflectometry

Abstract: Using molecular simulation to aid in the analysis of neutron reflectometry measurements is commonplace. However, reflectometry is a tool to probe large-scale structures, and therefore the use of all-atom simulation may be irrelevant. This work presents the first direct comparison between the reflectometry profiles obtained from different all-atom and coarse-grained molecular dynamics simulations. These are compared with a traditional model layer structure analysis method to determine the minimum simulation res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…To become more quantitative in comparing the simulations with experiments, we have calculated the neutron reflectivity curves emerging from the simulated structures. Indeed, the reflectivity and scattering curves of neutrons or X-rays provide a demanding test for membrane simulation 12,13,65 . Since our substrate model of layers and the coating beads were adjusted for the bare hydrated substrate (see Fig.…”
Section: Neutron Reflectivity Curves Of Dppc Slbsmentioning
confidence: 99%
“…To become more quantitative in comparing the simulations with experiments, we have calculated the neutron reflectivity curves emerging from the simulated structures. Indeed, the reflectivity and scattering curves of neutrons or X-rays provide a demanding test for membrane simulation 12,13,65 . Since our substrate model of layers and the coating beads were adjusted for the bare hydrated substrate (see Fig.…”
Section: Neutron Reflectivity Curves Of Dppc Slbsmentioning
confidence: 99%
“…In a more recent work, McCluskey et al [46] investigated whether the use of atomistic simulations are necessary to reproduce accurately experimental reflectometry data or whether coarse-grained representations are sufficient. By the comparison between the results obtained using different MD potential models and those originated from a traditional slab description of a monolayer sample, the authors concluded that discrepancy between simulations and experimental data are likely to be observed if the coarse-grained representation is too simplified.…”
Section: Simulation-based Methodsmentioning
confidence: 99%
“…Similarly, simulation or theory can generate continuous VF profiles. Examples include models derived from scaling theories (Field, Toprakcioglu, Dai et al, 1992;de Gennes, 1980), directly from molecular structure (McCluskey et al, 2019;Politsch et al, 2001;Politsch, 2001), from self-consistent field theory calculations (de de Vos & Leermakers, 2009) or from local cavity density functional theory calculations (Reinhardt et al, 2013). However, translation of these theoretical models to experiments is difficult because of the inherent variability of experimental systems (McCluskey et al, 2019).…”
Section: Parameterization Of Reflectometry Modelsmentioning
confidence: 99%